The synaptic vesicle protein SV31 assembles into a dimer and transports Zn2+. Issue 2 (5th December 2016) - Waberer, Lisa; Henrich, Erik; Peetz, Oliver; Morgner, Nina; Dötsch, Volker; Bernhard, Frank; Volknandt, Walter
Abstract : The synaptic vesicle Zn 2+ ‐binding protein SV31 functions as a proton‐dependent Zn 2+ transporter. Dimeric state, binding activity as well as stability are favored if SV31 is expressed in a lipid environment such as nanodiscs. Site‐directed mutagenesis of homologues amino acid residues involved in Zn 2+ ‐binding selected by comparison with a bacterial Zn 2+ transporter revealed two aspartic residues crucial for transport. Abstract: The integral synaptic vesicle protein SV31 has been shown to bind divalent cations. Here, we demonstrate that SV31 protein synthesized within a cell‐free system binds Zn 2+ and to a lower extent Ni 2+ and Cu 2+ ions. Expression with Zn 2+ stabilized the protein and increased solubility. SV31 was preferentially monomeric in detergent and revealed specific binding of Zn 2+ . When co‐translationally inserted into defined nanodisc bilayers, SV31 assembled into dimeric complexes, resulting in increased binding of Zn 2+ . Putative Zn 2+ ‐binding motifs within SV31 comprise aspartic acid and histidine residues. Site‐directed mutagenesis of two conserved aspartic acid residues leads to a potent decrease in Zn 2+ binding but did not affect dimerization. Chemical modification of histidine residues abolished some of the Zn 2+ ‐binding capacity. We demonstrate proton‐dependent transport of Zn 2+ as by accumulation of fluorescent FluoZin‐1 inside of SV31‐containing proteoliposomes. Transport activity has a K m value of 44.3 μM and required external Zn 2+ and internal acidic pH. Our results demonstrate that the synaptic vesicle‐integral protein SV31 functions as a proton‐dependent Zn 2+ transporter. SV31 may attribute specific and yet undiscovered functions to subsets of synapses.